Evaluasi Kinerja Pelayanan Publik pada Instansi Dinas Kependudukan dan Pencatatan Sipil di Kota Surabaya - Anggita Cahyani Setyoningrum; Nasya Firdaushaumy; Zahwa Laudia Mysah; Annisa Rahmawati; Attina Aulia Rahma; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (INDO PUBLISHING, 2026)
This study aims to evaluate the effectiveness of public services at the Department of Population and Civil Registration in Surabaya City. The main issue examined in this research is the quality of public services and the factors influencing service effectiveness. This study employs a qualitative method with a descriptive approach through literature review, by analyzing various sources such as scientific articles, books, official reports, and documents related to public services. The findings reveal that public services at the agency have generally shown positive development, particularly in terms of service accessibility, digital innovation, and responsiveness to the community. However, several challenges remain, including inadequate infrastructure, disparities in digital literacy among the public, and the high number of service users, which affect service effectiveness. Therefore, continuous improvement efforts are needed through enhancing human resource quality, optimizing technology-based service systems, and strengthening facilities and infrastructure to improve the overall quality of public services.